Sex Differences in Collateral Circulation and Outcome After Mechanical Thrombectomy in Acute Ischemic Stroke - Lagebrant, Christian; Ramgren, Birgitta; Hassani Espili, Ashkan; Marañon, Antonio; Kremer, Christine (Frontiers in Neurology, 2022)
Background Collateral circulation is known to lead to smaller infarct volume and better functional outcome after mechanical thrombectomy (MT), but studies examining sex differences in collateral circulation are scarce. The aim of this study was to investigate if collateral circulation has a different impact on outcome in women and men. Methods A single-center retrospective study of 487 patients (230 men and 257 women) treated with MT for acute ischemic stroke in the anterior cerebral circulation. Collateral circulation was assessed on computed tomography angiography images. The outcome was evaluated at 90 days according to the modified Rankin Scale (mRS). Results Women were older, median age 76 years (IQR 68-83) vs. 71 years (IQR 63–78). Stroke severity and time to recanalization were comparable. More women had moderate or good collaterals in 58.4 vs. 47.0% for men (p = 0.01). Among patients with moderate and good collaterals significantly more men (61%) were functionally independent (mRS 0–2) than women (41.5%) (p = < 0.01). This difference remained significant after correcting for age by linear weighting, 60.4 vs. 46.8% (p = 0.03). Conclusion Women had better collateral flow but showed worse functional outcomes, while good collateral flow led to better outcomes in men, even after correcting for age. Further clinical studies on peri- and post-interventional care, factors affecting recovery after hospital discharge as well as basic research on the neurovascular unit are needed to find modifiable targets to improve clinical outcomes for women.